Defining Learning Objectives from the Perspectives of Al-Qur’an - Abd Mukti; Achyar Zein; Jamel Jamel (AL-ISHLAH: Jurnal Pendidikan, 2022)
The value of the learning objectives used by the teacher in the lesson plans in the learning process must require that the Al-Qur’an. It is used as a book of instructions and a source of knowledge in explaining the learning objectives that should be included in the lesson plans. This research is a literature study (library research). The data sources in this study consisted of primary data in the form of the Qur'an Surah al-Baqarah (verses 31, 32, 102, 129, 151, 239, 251), Surah Ali Imran (verses 48, 79, 164), and Surah An-Nisa ( verse 113). While secondary data in the form of books of interpretation of al-Qur'anul Madjid An-Nur, interpretation of the Qur'an Karim, interpretation of al-Azhar and interpretation of al-Mishbah as well as books of science and philosophy of Islamic education that have relevance and significance to the topic of this research, namely learning objectives in the Koran. The method used in the data analysis of this research is the thematic interpretation method (tafsir maudu'iy). The results of the descriptive analysis reveal that linguistically the Koran uses the terms ta'lim, tadris and tarbiyah, to express the word learning. Meanwhile, to express the purpose, the Qur'an uses the term maqasid, namely muqtasidah, qasidan, qas'd, iqsid and muqtasid. All these terms implicitly contain the meaning of the goal, namely the formulation that will be achieved on the basis of the cognitive, affective and psychomotor domains, which are the targets to be achieved after the completion of the learning process, and can motivate students in carrying out the learning process.